Total hordatine content in different types of beers. Issue 2 (6th April 2016) - Pihlava, Juha‐Matti; Kurtelius, Tuula; Hurme, Timo
Abstract: Hordatines are phenolic secondary metabolites typical of barley. Hordatines withstand at least moderate processing, and thus they are also found in barley malts and beer. So far, no published data on the hordatine content has been available in beers or different styles of beer. The aim of this study was to produce information on the total hordatine content in beers and statistically compare the hordatine content of different beer types. In the current study, hordatines were analysed in 208 beers by high‐performance liquid chromatography equipped with a diode array detector (HPLC‐DAD). The average total hordatine content of all beer samples was 5.6 ± 3.1 mg L −1 as p ‐coumaric acid equivalents (PCAE), with a minimum values 0 to a maximum value 18.7 mg L −1 PCAE. The total hordatine content correlated positively to the alcohol content in lagers, ales, stouts and porters, but not in wheat beers. There was no statistically significant difference in hordatine content in different types of beer, excluding the non‐alcoholic group of beers. It is noteworthy that non‐alcoholic beers also contained hordatines. More research would be needed to understand how parameters, such as mashing, should be chosen in order to achieve maximum recovery of hordatines in wort and beer.